Sur l’origine de l’écriture libyque. Quelques propositions - Dominique Casajus (Afriques)
A few hypotheses about the origin of the so-called “Libyan” alphabets are presented. Attested in more than a thousand inscriptions from Libya to the Canary Islands in northern Africa, these alphabets are probably the forebears of the current ones used by the Tuareg. The only inscription that has been dated (139 BCE) with a reasonable degree of certainty is bilingual, Libyco-Punic, from Dougga in Tunisia. The “Libyan” alphabets apparently already existed, several centuries earlier. Their creators borrowed a few — at least four — letters from the Phoenician/Punic alphabets; and apparently used simple geometric procedures, which are reconstituted herein, for the other letters.